The development of education in China in the twentieth century and an overview of the reforms (Journal of Educational Sciences, 2017)
The article describes the development and reform of China in the twentieth century, proposed a рeriodization of the development. Based on the analysis of scientific pedagogical literature highlighted two periods of development – reform of the Old China (1901 - 1949) and reform of New China (1949 – present). In the first period allocated to the 4 stages: the reform of the education system Genuine,Guimo; reform of the education system «663» close to the American model; the reform of the education system «Uzen», the reform of military time. In the second period is called the period of the New China, selected in 7 stages: from the creation of the state system of education, people’s Republic of China, the revolution ofthe enlightenment, cultural revolution, and decay; the restoration of the education system «663», its diversification; strategic development and reform of the education system, aimed at improving socialism with Chinese characteristics. The trajectory of the reform and development of pedagogical theories of the twentieth century the veil on the political situation in China, the scientific and technological revolution and industrial development of China. Pedagogical science China substantial borrowed Western – American and European approaches, as well as in revolutions – socialist direction and the ideology of development, adapting to your conditions.
Keywords: education reform; history of education; trends of educational development